Multi-technique surface geophysical surveys over Devon Ice Cap, Canadian Arctic - Siobhan F Killingbeck; Martyn J Unsworth; Anja Rutishauser; Ashley Dubnick; Alison S. Criscitiello; James Killingbeck; Christine F Dow; Tim Hill; Adam D Booth; Brittany Main; Eric Brossier (Zenodo, 2023)
This dataset was acquired during a multi-technique surface geophysical campaign in May 2022 over Devon Ice Cap, Canadian Arctic. Description of data: Seismic 9 km of active source seismic reflection data raw segy files for line A and line B seismic observation log matlab script for plotting a raw stack of line A and line B coordinates of each seismic spread, with the ice surface elevation and estimated bed elevation Transient electromagnetic (TEM) 7 large loop TEM soundings with 500 x 500 m loop with receiver 250 m outside the loop (away from the transmitter) USF files for each sounding coordinates for each TEM sounding TEM observation log Magnetotelluric (MT) 17 MT stations raw, unprocessed EDI files coordinates for each MT station MT observation log Time series data (~80GB) can be found at: https://drive.google.com/drive/folders/1OyCIP_B3VUJ4-ULSp8YOAPuNEMHuNcN-?usp=share_link Acknowledgments We thanks the Polar Continental Shelf Program for logistical support throughout the field season; Rob Harris at Geonics for his support and help with the TEM method; Zoe Vestrum at the University of Alberta for her MT support during deployment to the field; Funding This work was funded by the Weston Family Foundation. The aircraft hours were funded by the Polar Continental Survey Program (PCSP) and ArcticNet. MT survey was supported by a NSERC Discovery Grant to Martyn Unsworth and the Future Energy Systems program at the University of Alberta. Corresponding Author Siobhan Killingbeck skillin1@ualberta.ca